Aktivitas Antibakteri Ekstrak Momordica charantia L. terhadap Staphylococcus aureus dan Salmonella thypi - Waris, Muhammad Anugerah Alam; Aris, Muhammad; Syarif, Muhammad (NUTRITURE JOURNAL; Vol 2 No 1 (2023): Jurnal NutritureDO - 10.31290/nj.v2i1.3852, 2023)
Momordica charantia L. contains flavonoids, saponins, and alkaloids. This study aims to determine the inhibition of M. charantia extract on the growth of S. aureus and S. thypi and the highest concentration in inhibiting S. aureus and S. thypi. Then extracted by maceration method with 96% ethanol solvent. M. charantia extracts prepared in concentrations of 2.5%, 5% and 7.5% were tested on S. aureus and S. thypi cultures, CMC Na as a negative control and Cefadroxil as a positive control. Determination of the inhibition zone was carried out by the diffusion method using a paper disk on Nutrient Agar (NA) media with an incubation period of 1 x 24 hours at 37 C. The diameter of the inhibition zone on S. aureus resulted in an average concentration of 2.5% (5.2 mm), concentration of 5% (5.23 mm), and concentration of 7.5% (7.36 mm), the negative control did not produce an inhibition zone while the positive control was 18.96 mm. Whereas S. thypi produced an inhibition zone with an average concentration of 2.5% (8.1 mm), 5% concentration (9.46 mm) and 9.5% concentration (17.06 mm), and in the control the negative inhibition zone was not visible while the positive control had an inhibition zone of 19.06 mm.